Development of equipment for the research quantitative and qualitative characteristics of pectin concentrates - Дейниченко, Григорій Вікторович; Афукова, Наталия Александровна; Мазняк, Захар Александрович; Гузенко, Василий Владимирович (Technology audit and production reserves, 2014)
The research paper is devoted to the new approach to the issue of technical equipment of the research base in the process of determining of quantitative and qualitative characteristics of pectin extracts, concentrates and other pectin-containing products. The role of pectin substances in human life, as well as the current state of development of various pectin products production and problems of their further storage is described. The necessity of creating new laboratory equipment for studying of qualitative and quantitative characteristics of the obtained pectin extracts and concentrates is determined. The results of patent search of the existing laboratory equipment for studying of the process of plant raw material extraction are presented and their disadvantages are described. New laboratory equipment for producing pectin extracts from pectin-containing plant raw material and their further studying is elaborated. The device of the elaborated equipment and its operating principle is described. The elaborated equipment can be used in food, pharmaceutical and microbiological industry during laboratory studies of various carbohydrates (pectin substances, starch, fiber and other dietary fibers), lipids, vitamins and other substances which require conversion of soluble substance to solvent.